Mechanism of calcium potentiation of the α7 nicotinic acetylcholine receptor - Natarajan, Kathiresan (2020)
The α7 nicotinic acetylcholine receptor (nAChR) is among the most abundant types of nAChR in the brain, yet the ability of nerve-released ACh to activate α7 remains enigmatic. In particular, a major population of α7 resides in extra-synaptic regions where the ACh concentration is reduced, owing to dilution and enzymatic hydrolysis, yet ACh shows low potency in activating α7. Using high-resolution single-channel recording techniques, we show that extracellular calcium is a powerful potentiator of α7 activated by low concentrations of ACh. Potentiation manifests as robust increases in the frequency of channel opening and the average duration of the openings. Molecular dynamics simulations reveal that calcium binds to the periphery of the five ligand binding sites and is framed by a pair of anionic residues from the principal and complementary faces of each site. Mutation of residues identified by simulation prevents calcium from potentiating ACh-elicited channel opening. An anionic residue is conserved at each of the identified positions in all vertebrate species of α7. Thus, calcium associates with a novel structural motif on α7 and is an obligate cofactor in regions of limited ACh concentration.